Insights on the HLA-G Evolutionary History Provided by a Nearby Alu Insertion - Santos, Kaisson E.; Lima, Thalitta H. A.; Felicio, Leandro P.; Massaro, Juliana D.; Palomino, Gustavo M.; Silva, Ana Carolina A.; Oliveira, Silviene F.; Sabbagh, Audrey; Garcia, Andre; Moreau, Philippe; Donadi, Eduardo A.; Mendes-Junior, Celso T.; et al. (Oxford University Press, 2013)
The AluyHG element belongs to the AluYb8 subfamily. It is a polymorphic insertion, located approximately 20 kb from the HLA-G 3'-untranslated region (3'-UTR), which has been used for evolution studies because it exhibits identity for descendants and it is still polymorphic in the human genome. To understand the evolutionary mechanisms acting on HLA-G, we evaluated the presence or absence of the AluyHG element, associating this variable site with others observed at HLA-G coding, 3'-UTR, or both regions in four distinct populations (Brazilian, French, Congolese, and Senegalese). The results were compared with the 1000Genomes Consortium data. The worldwide AluyHG frequencies showed an increment, starting lower in Africa and increasing following distance and time of human dispersion out of Africa. The same haplotype pattern was observed in all populations, indicating that most of the HLA-G haplotypes already detected were originated earlier in Africa, before Homo sapiens dispersion. The AluyHG insertion was associated with the G*01:01:01:01/UTR-1 haplotype, with rare recombinants. Despite its high frequency in worldwide populations, the G*01:01:01:01/UTR-1 haplotype should be very recent. The low frequency of recombinants indicates that the rate of recombination at the HLA-G gene is very low.
Keywords: AluyHG; HLA-G; 3'-untranslated region; haplotypes; worldwide diversity; human evolution